Association of Vitamin D With Insulin Resistance and β-Cell Dysfunction in Subjects at Risk for Type 2 Diabetes - Kayaniyil, Sheena (American Diabetes Association, 2010)
OBJECTIVE: To examine cross-sectional associations of serum vitamin D [25-hydroxyvitamin D, 25(OH)D] concentration with insulin resistance (IR) and β-cell dysfunction in 712 subjects at risk for type 2 diabetes. RESEARCH DESIGN AND METHODS: Serum 25(OH)D was determined using a chemiluminescence immunoassay. Insulin sensitivity/resistance were measured using the Matsuda insulin sensitivity index for oral glucose tolerance tests (IS(OGTT)) and homeostasis model assessment of insulin resistance HOMA-IR. β-Cell function was determined using both the insulinogenic index (IGI) divided by HOMA-IR (IGI/IR) and the insulin secretion sensitivity index-2 (ISSI-2). RESULTS: Linear regression analyses indicated independent associations of 25(OH)D with IS(OGTT) and HOMA-IR (β = 0.004, P = 0.0003, and β = −0.003, P = 0.0072, respectively) and with IGI/IR and ISSI-2 (β = 0.004, P = 0.0286, and β = 0.003, P = 0.0011, respectively) after adjusting for sociodemographics, physical activity, supplement use, parathyroid hormone, and BMI. CONCLUSIONS: Vitamin D may play a role in the pathogenesis of type 2 diabetes, as 25(OH)D concentration was independently associated with both insulin sensitivity and β-cell function among individuals at risk of type 2 diabetes.